Ace school

with brainly

  • Get help from millions of students
  • Learn from experts with step-by-step explanations
  • Level-up by helping others

A community for students.

Choose the equation of the line passing through the point (-1, 3) and perpendicular to y = -negative one thirdx + 7. y = 3x - 12 y = 3x + 6 y = 3x - 6 y = 3x

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

first we need to find the slope of the equation given. y = -1/3x + 7 (In y = mx + b form, the m is the slope. Therefore, the slope of this line is -1/3) But we need a perpendicular line, so we need the negative reciprocal of that slope. All that means is " flip " the slope and change the sign. The negative reciprocal of -1/3 = 3/1 or just 3 (you see how I flipped the slope and changed the sign) so we have slope(m) = 3 (-1,3) x = -1 and y = 3 y = mx + b and solve for b 3 = 3(-1) + b 3 = -3 + b 3 + 3 = b 6 = b your perpendicular line is : y = 3x + 6
Thank you so much. will you help on another ?
sure :)

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

hoose the equation of the line passing through the point (-3, 1) and parallel to y = -x - 4. y = x + 2 y = -x - 2 y = -x + 4 y = x - 4
y = -x - 4 (slope is -1) Since we need a parallel slope, the original slope stays the same. slope(m) = -1 (-3,1) x = -3 and y = 1 y = mx + b for b 1 = -1(-3) + b 1 = 3 + b 1 - 3 = b -2 = b your parallel line is : y = -x - 2
any questions ?
Since you worked it out I understand now.. Thanks you (:
anytime :)

Not the answer you are looking for?

Search for more explanations.

Ask your own question